Finite element analysis of the behavior of bonded composite patches repair in aircraft structures (Fracture and Structural Integrity, 2020)
This paper aims to analyze the multi-effects of the glass fiber reinforced polymer (GFRP) composite patch to repair the inclined cracked 2420-T3 aluminum plate. Three-dimensional finite element method (FEM) was used to study the effect of GFRP composite patch with different stacking composite laminate sequence, [0°]4, [90o]4, [45o]4, [0o/45o]2s and [0°/90°]4s on the crack driving force, J-integral, of inclined cracked 2420-T3 aluminum plate. Furthermore, the effects of patch geometry, number of layers, single or double side patch and crack incline angle are described.The present results show that the patch has a high effect in case of a crack in pure mode I. Furthermore, the effectiveness of the composite patch is increasing with the crack length increases. Moreover, the efficiency of the composite patch has a high effect by changing the fiber orientation, the number of layers, and the single or double side patch.
Keywords: Mode of mixity; J-integral; Aluminum alloy; 3-D FEM; Composite repair patch